Generalized congenital myofibromatosis with central nervous system involvement. - Bonifazi, E.; Filotico, R.; Mazzotta, F.; Ruggiero, G.; Modesti, A. (European Journal of Pediatric Dermatology, 2018)
A case of generalized congenital myofibromatosis with central nervous system involvement is reported. In spite of the severe clinical features, all the lesions including the nervous ones spontaneously regressed within 2 1 /2 years. This case underlines the fact that visceral lesions are not always associated with a bad prognosis. The clinical course of congenital myofibromatosis is reminiscent of that of other hamartomatous proliferations characteristic of the first months of !ife, such as mastocytosis, juvenile xanthogranuloma and Langerhans cell histiocytosis. This close likeness does not support the hypothesis that the pathogenesis and the spontaneous regression of congenital myofibromatosis is linked with the particular proliferating cell, namely the myofibroblast.